Correlation between Gleason scores in needle biopsy and corresponding radical prostatectomy specimens. A twelve-year review. - Maliheh Khoddami; yassaman Khademi; Maryam Kazemi Aghdam; Haleh Soltanghoraee (Iranian Society of Pathology, 2016)
Background: Presence of discordance between the Gleason score on needle biopsy and the score of radical prostatectomy specimen is common and universal. In this study, we determined the accuracy of Gleason grading of biopsies in predicting histological grading of radical prostatectomy specimens and the degree of overgrading and undergrading of prostatic adenocarcinoma in our center, which is one of the referral centers in Tehran. Methods: In this retrospective study, we analyzed the results of prostate needle biopsies and subsequent prostatectomies diagnosed at the Pathobiology Laboratory Center, Tehran, Iran in 45 patients between 2002 and 2013. Preoperative clinical data and theinformation from biopsy and prostatectomy specimens were collected.The accuracy, sensitivity, specificity, and positive and negative predictive values of different grades and groups were assessed. Pearson and Spearman correlation coefficient were used to determine the relation of different variables. Results: The biopsy Gleason score was identical to the scores in prostatectomy specimens in 68.2% cases, while 31.8% were discrepant by 1 or 2 Gleason score. We had 9.1% downgrading and 22.7% cases upgraded after prostatectomy. The sensitivity and positive predictive value was 86% and 79% for low grade, 67% and 75% for moderate grade, and 80% and 80% for high-grade tumors, respectively. Conclusion: Overall, the reliability of Gleason grading of needle biopsies in predicting final pathology was satisfavory. Moderate grade group was the most difficult to diagnose in needle biopsy.